Synthesis and Thermal Performance of Microencapsulated Binary Carbonate Molten Salts for Solar Thermal Energy Storage - Lee, Jaejun; Jo, Byeongnam (Energy and Fuels, 2021)
High-temperature thermal energy storage (TES) is necessary for balancing energy demand and supply in concentrating solar power plants and also for reducing the preheating load in thermal power stations to lower the ultimate production cost of electricity. This study aimed to develop surfactant-free synthesis protocols for the microencapsulation of a binary carbonate eutectic (Li2CO3and K2CO3at a 28:72 mass ratio) in silica shells using a sol-gel process and to examine the thermal properties and thermal reliability of the resulting microencapsulated carbonate eutectic. The effects of solvent properties (solvent type and polarity) on the microencapsulation of carbonate salts were examined using ethanol, isopropanol, and acetone. The most stable chemical structures for the silica shell and the best thermal performance were achieved by the microcapsules synthesized using acetone. The encapsulation ratio of the carbonate microcapsules was 64.2%. Scanning electron microscopy and Fourier transform infrared spectroscopy analyses revealed that the morphological and chemical characteristics of the microcapsules were maintained after repeated thermal cycles (heating and cooling) between 250 and 540 °C. Additionally, a consistent amount of heat was stored and released in the carbonate eutectic microcapsules, regardless of the ramping/cooling rates (5, 10, and 20 °C/min), with rapid temperature transitions. Phase-change performance was preserved at approximately 97.4% of the initial value, even after 100 thermal cycles. The volumetric TES capacity was enhanced by 91.1% compared to that of solar salts with regard to the thermophysical properties of the microcapsules. Additionally, the thermal conductivity of the microcapsule was enhanced by 39.9% compared to that of the pure carbonate eutectic. In summary, the high-temperature stability and reliability of the synthesized microcapsules and their rapid charging/discharging performance demonstrate the applicability of molten salt microcapsules as storage media in high-temperature TES applications.
Keywords: Chemical characteristic; Concentrating solar power plant; Heating and cooling; High temperature stability; High temperature thermal energy storages; Solar thermal energy; Thermal Performance; Thermal power stations